Analysis of MARPOL 73/78 Annex V Policy in Controlling Dry Bulk Residues on Cargo Ships at Gresik Port Terminal - Muhammad Alifandra Noufal Rizky; Achmad Zahiduz Zaka; Maulana Adi Triaksa; Muhammad Rafly Rosandi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Maritime pollution from dry bulk cargo residues threatens marine ecosystems and requires strict control through the international convention MARPOL 73/78 Annex V. To analyze the implementation effectiveness of MARPOL 73/78 Annex V policy in controlling dry bulk residues on cargo vessels at Gresik Port Terminal, identify barriers, and formulate recommendations for compliance enhancement. Descriptive qualitative research utilizing direct observation techniques, in-depth interviews with ship crews and port officials, and documentation study on five dry bulk cargo vessels. Results: Implementation effectiveness reached 79% (good category) with highest compliance on regulatory documentation availability (100%) but constrained by port waste reception facilities infrastructure (40%) and residue management systems (76%). Primary barriers include limited storage capacity, waste separation complexity, and crew competency gaps. Optimization requires strengthened enforcement, integrated infrastructure development, technical standardization, and human resource capacity enhancement through multi-stakeholder collaboration.